2008
DOI: 10.1007/s11205-008-9299-3
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence of the Postmaterialist Shift: The Experience of Hong Kong

Abstract: Postmaterialism, Modernization, Social development, Value orientation, Hong Kong,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…He thus argued that political leaders and governments under Confucian culture occupy an important symbolic authoritative status in society, and that the worship, sensitivity, and dependence of the people towards authority could easily have a profound effect on their political trust. Moreover, other scholars observed that the transition from materialism to post-materialism seen in many advanced countries of the West is also appearing in such Asian societies as Taiwan, Hong Kong, and China and beginning to have an impact on political trust in these places (Hsiao and Wan, 2004; Wang, 2005; Wong and Wan, 2008b). Such findings show that improvements in socio-economic conditions may not necessarily strengthen people's trust in their government and political system.…”
Section: Determinants Of Political Trustmentioning
confidence: 99%
“…He thus argued that political leaders and governments under Confucian culture occupy an important symbolic authoritative status in society, and that the worship, sensitivity, and dependence of the people towards authority could easily have a profound effect on their political trust. Moreover, other scholars observed that the transition from materialism to post-materialism seen in many advanced countries of the West is also appearing in such Asian societies as Taiwan, Hong Kong, and China and beginning to have an impact on political trust in these places (Hsiao and Wan, 2004; Wang, 2005; Wong and Wan, 2008b). Such findings show that improvements in socio-economic conditions may not necessarily strengthen people's trust in their government and political system.…”
Section: Determinants Of Political Trustmentioning
confidence: 99%
“…From the 2014 Taiwan and Hong Kong movements, we can see that a transformation in social values was a major reason for why young people took part in these protest actions. Young people obviously place a high priority on democracy, freedom, self-determination, justice, and other post-materialist values (Chang and Chen, 2013; Theocharis, 2011; Wong and Wan, 2009). However, this round of “new social movements”, which sprang from this transformation in social values and which was also characterized by the greater prominence of social concern and personal participation in the “new politics”, is not a departure from traditional democratic movements.…”
Section: Resultsmentioning
confidence: 99%
“…Prior researchers have identified barriers to obtaining data of this kind from Hong Kong based respondents (Shenkar, 1994;Wong & Wan, 2009). We had, accordingly, worked around access barriers by adopting 'snowballing' (Brannen, 1988), starting with trusted acquaintances of members of the research team.…”
Section: Source Of and Methods Adopted For The Hitherto Unpublished Case Materialsmentioning
confidence: 99%